The Healthy Home Offerings via the Mealtime Environment (HOME) Plus study: Design and methods() - Fulkerson, Jayne A. (2014)
BACKGROUND: Informed and engaged parents and healthful home environments are essential for the health of youth. Although research has shown health benefits associated with family meals, to date, no randomized controlled trial (RCT) has been developed to examine the impact of a family meals intervention on behavioral and health outcomes. METHODS/DESIGN: The Healthy Home Offerings via the Mealtime Environment (HOME) Plus study is a two-arm (intervention versus attention-only control) RCT being conducted in Minneapolis/St. Paul. Built on previous pilot research, HOME Plus aims to increase the frequency and healthfulness of family meals and snacks and reduce children’s sedentary behavior, particularly screen time, to promote healthier eating and activity behaviors and prevent obesity. HOME Plus is delivered to families in community settings. The program includes 10 monthly sessions focused on nutrition and activity education, meal planning and preparation skill development. In addition, five motivational goal-setting phone calls are conducted with parents. The primary outcome measure is age- and gender-adjusted child BMI-z score at post-intervention by treatment group. Secondary household-level outcomes include family meal frequency, home availability of healthful foods (fruits/vegetables) and unhealthful foods (high-fat/sugary snacks) and beverages (sugar-sweetened beverages), and the quality of foods served at meals and snacks. Secondary child outcomes include dietary intake of corresponding foods and beverages and screen time. CONCLUSIONS: The HOME Plus RCT actively engages whole families of 8–12 year old children to promote healthier eating and activity behaviors and prevent obesity through promotion of family meals and snacks and limited media use.